Robot-Assisted Nephroureterectomy for Upper Tract Urothelial Carcinoma in a Patient with an Ileal Conduit - Raymond A. Stemrich; Neel Hasmukh Patel; Jacob A. Baber; Mark J. Ferretti (Case Reports in Urology)
Background. Upper tract urothelial carcinoma remains an uncommon disease that is clinically difficult to identify early and surveil. Open nephroureterectomy is the gold standard for patients with high-grade disease, especially for patients in whom surveillance is complicated such as those with prior cystectomies/ileal conduits. This report presents a case of a patient with a history of radical cystectomy and ileal conduit construction who underwent a successful minimally invasive robotic surgery for treatment of upper tract urothelial carcinoma. Case Presentation. The patient is a 72-year-old Caucasian male with a history of recurrent superficial bladder tumors treated with cystoscopies with fulguration, Bacillus Calmette-Guerin, and a robot-assisted cystectomy with ileal conduit diversion presenting with recurrent urinary tract infections and hematuria secondary to a ureteral stricture. The patient was admitted previously for urosepsis during which time a percutaneous nephrostomy tube was inserted on the right side. Upon presentation, imaging revealed a lesion extending from the lower pole of the right kidney into the renal pelvis. The presence of a nephrostomy and urostomy allowed the surgical team to utilize a minimally invasive approach to remove the diseased kidney and ureter with visualization enhanced by indocyanine green. Conclusion. Minimally invasive robot-assisted approaches to treating upper tract urothelial carcinomas may offer an alternative to the open cases typically employed in cases of patients with prior ileal conduit. Furthermore, utilizing indocyanine green may expand the applicability of such approaches to uro-oncologic cases with greater complexity.